2010
DOI: 10.1074/jbc.m110.164731
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-induced EGF Receptor Oligomerization Is Kinase-dependent and Enhances Internalization

Abstract: The current activation model of the EGF receptor (EGFR) predicts that binding of EGF results in dimerization and oligomerization of the EGFR, leading to the allosteric activation of the intracellular tyrosine kinase. Little is known about the regulatory mechanism of receptor oligomerization. In this study, we have employed FRET between identical fluorophores (homo-FRET) to monitor the dimerization and oligomerization state of the EGFR before and after receptor activation. Our data show that, in the absence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
110
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(119 citation statements)
references
References 30 publications
7
110
1
Order By: Relevance
“…Direct predimerization, at least among ErbB3 molecules, has been reported previously (11,14). Predimerization has also been detected for ErbB1 (32). Therefore, we assumed that the two-step association sites were predimers of HRG receptors in the kinetic models.…”
Section: Discussionmentioning
confidence: 99%
“…Direct predimerization, at least among ErbB3 molecules, has been reported previously (11,14). Predimerization has also been detected for ErbB1 (32). Therefore, we assumed that the two-step association sites were predimers of HRG receptors in the kinetic models.…”
Section: Discussionmentioning
confidence: 99%
“…This model has been supported by crystal structures of the extracellular domain of EGFR (7,8) as well as by reports of EGFR dimerization after stimulation with EGF. However, numerous studies have also reported the presence of EGFR dimers or even larger oligomers in the membranes of resting cells (9)(10)(11)(12)(13). The presence of preformed EGFR dimers and oligomers indicates that regulation of EGFR signaling is more complex than implied by the model outlined above (Fig.…”
Section: Introductionmentioning
confidence: 93%
“…Quantitation of EGF receptor expression in each line by 125 I-EGF saturation binding indicated that the number of cell surface EGF receptors expressed in each line is within Ϯ20% of the average level of receptor expression (data not shown). Cells were grown in Dulbecco's modified Eagle's medium supplemented with 10% FetalPlex, 100 g/ml G418, 100 g/ml hygromycin, and 100 g/ml Zeocin and maintained in an incubator at 37°C in 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…In the absence of ligand, the EGF receptor is thought to exist as a monomer, although inactive "pre-dimers" are known to form (1)(2)(3)(4)(5). Upon binding an agonist ligand, the EGF receptor dimerizes leading to the activation of its tyrosine kinase and the phosphorylation of tyrosine residues in the C-terminal tail of the receptor (6 -8).…”
mentioning
confidence: 99%